Analisa Kesulitan Siswa Kelas XI dalam Pembelajaran Kimia di Sman 1 Masbagik - Fena Prayunisa (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
The purpose of this research is to analyze the students of SMA Class XI IPA in learning chemistry at SMAN 1 Masbagik. This research is a qualitative research method, where the instruments used are interviews and student statements. The subjects in this study were students of class XI SMAN 1 Masbagik who opened 84 people. There are several factors that cause students to be less interested and less fond of chemistry lessons, including: 1) Internal factors are factors that come from within students. 2) External factors that can come from teachers, learning methods and also colleagues. Based on the data from the questionnaire above which was distributed to each student of class XI Natural Sciences, both students and students who found 84 people, obtained some data stating that learning in class was fun only 53%, who liked chemistry lessons only 30% and only 30% who understands chemistry. There are two possibilities, it means that chemistry lessons are very difficult to understand and they are forced to study chemistry because it is a compulsory subject in science